THE INFLUENCE OF FUNCTIONAL VALUES, SOCIAL VALUES, AND HEDONIC MOTIVATION ON REPURCHASE INTENTION OF VIRTUAL GOODS IN ROBLOX USERS AMONG GENERATION Z SURABAYA - Permatasari, Sherly Della; Samsudin, Acep (Jurnal Ilmiah Ekonomi Bisnis, 2026)
The purpose of this study is to investigate whether or not Generation Z Surabaya Roblox users' interest in purchasing virtual items is influenced by hedonic motives, social values, and functional values. Quantitative methods based on an associative research design are used in this study. The 156 subjects included in this research were selected using a non-probability selection method. Data was collected by a questionnaire, and it was analyzed using multiple linear regression. Hedonic motivation, social values, and functional values all have a favorable and substantial influence on repurchase intention simultaneously, according to the study. Functional value has a favorable and substantial effect on repurchase intention. The influence of societal values on repurchase intention is favorable and substantial. In a favorable and statistically significant way, hedonic motivation influences the desire to repurchase intention.